The Delphi technique : its methodology and potential for educational planners in developing countries : a thesis presented in partial fulfilment of the requirements for the degree Master of Education at Massey University - Sarr-Cessay, Mariama (Massey University, 1982)
This study had two objectives: (i) To examine methodological difficulties in using the Normative Delphi Technique as a tool for educational planners; and (ii) To explore the potential of the Normative Delphi Technique for educational planners in Developing Countries. To achieve the above objectives, an experimental-type Delphi was carried out, using a group of fourteen New Zealand experts in the field of Educational Planning, who had worked as consultants or advisers in Developing Countries. A three phase Delphi procedure was employed combined with a follow-up evaluation of the study by the respondents. On the basis of this experimental Delphi study it was concluded that the Technique may be potentially viable as an instrument for gaining consolidation and consensus of respondent opinion, but that methodological difficulties exist within the Technique. These include : the selection of subjects, character and clarity of Round One, type and effect of information feedback and the number of rounds used. It was suggested that these difficulties could easily be overcome and that,the Delphi Technique may complement, and indeed expedite existing educational planning procedures in Developing Countries such as Commissions of Enquiry, Ministry Plans and Research Studies.
Keywords: Delphi method; Decision making; Developing countries; Educational planning